Analysis and Modeling of Laser Beam Melt Ablation - Cser, Adrienn Orsolya; Otto, Andreas (AMST 05: Advanced Manufacturing Systems and Technology: Proceedings of the 7th International Conference, 2005)
Laser beam melt ablation as a non-contact process offers several advantages compared to conventional processing mechanisms. During ablation the surface of the workpiece is molten by the energy of a CO2-laser beam. This melt is then driven out using the momentum transfer from an additional process gas flow. Although the idea behind laser beam melt ablation is rather simple, the process itself has a major limitation in practical applications: with increasing ablation rate, the surface quality of the processed workpieces declines rapidly. To find an explanation, and to be eventually be able to control the process thorough analyses are necessary. For this, in addition to the measurements of the processed surfaces also the optical process emissions have been recorded and analyzed. These data show a pronounced 1/f-noise-like behavior, which suggests the existence of intermittency during processing.
LFT Import::2019-08-05 (1176)
Keywords: Control; Laser ablation; Modeling